2022
DOI: 10.48550/arxiv.2205.07577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rotating Love: The dynamical tides of spinning Newtonian stars

Abstract: We develop the framework required to model the dynamical tidal response of a spinning neutron star in an inspiralling binary system, in the context of Newtonian gravity. The tidal perturbation is decomposed in terms of the normal oscillation modes, used to derive an expression for the effective Love number which is valid for any rotation rate. Our analysis highlights subtle issues relating to the orthogonality condition required for the mode-sum representation of the dynamical tide and shows how the prograde a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 149 publications
0
0
0
Order By: Relevance
“…In particular, recent gravitational waveform modelling developments include the dynamical tidal correction due to the excitation of NS f-modes [31,32,104,105]. Recently in [31], by considering the state of the art effective one body (EOB) model TEOBResumS, it has been shown that due to the noise dominance in the higher frequency range of GW170817, both waveform model with and without f-mode dynamics behave similarly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, recent gravitational waveform modelling developments include the dynamical tidal correction due to the excitation of NS f-modes [31,32,104,105]. Recently in [31], by considering the state of the art effective one body (EOB) model TEOBResumS, it has been shown that due to the noise dominance in the higher frequency range of GW170817, both waveform model with and without f-mode dynamics behave similarly.…”
Section: Discussionmentioning
confidence: 99%
“…Although we ignore the spin and eccentricity, it was suggested that spin and eccentricity further enhance the excitation of f-modes in binary [30]. However, the corrections to the f-mode dynamical tide due to spin and eccentricity are still matter of investigation and recent efforts are going on this direction [30,104,105,108].…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that the Keplerian orbital frequency is much smaller than the relativistic frequency c/R when the two objects are far from each other, so the orbital frequency and the frequency of the internal mode can be equal only if the frequency of the mode satisfies ω ≪ c/R. Tidal resonant excitations were first discussed in the context of ordinary polytropic stars [38], then, much later, for binaries with at least one of the companions being a neutron star [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The case in which companion is a generic compact object was discussed in [54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%